The SAMI Galaxy Survey : spatially resolving the environmental quenching of star formation in GAMA galaxies - Schaefer, A. L.; Croom, S. M.; Allen, J. T.; Brough, S.; Medling, A. M.; Ho, I. -T.; Scott, N.; Richards, S. N.; Pracy, M. B.; Gunawardhana, M. L. P.; Norberg, P.; Alpaslan, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We use data from the Sydney-AAO Multi-Object Integral Field Spectrograph Galaxy Survey and the Galaxy And Mass Assembly (GAMA) survey to investigate the spatially resolved signatures of the environmental quenching of star formation in galaxies. Using dust-corrected measurements of the distribution of H α emission, we measure the radial profiles of star formation in a sample of 201 star-forming galaxies covering three orders of magnitude in stellar mass (M∗;108.1 –1010.95 M⊙ ) and in fifth nearest neighbour local environment density (Σ5;10−1.3 –102.1 Mpc−2 ). We show that star formation rate gradients in galaxies are steeper in dense (log10(Σ5/Mpc2) > 0.5) environments by 0.58 ± 0 . 29 dex re−1 in galaxies with stellar masses in the range 1010 < M∗ / M⊙ < 1011 and that this steepening is accompanied by a reduction in the integrated star formation rate. However, for any given stellar mass or environment density, the star formation morphology of galaxies shows large scatter. We also measure the degree to which the star formation is centrally concentrated using the unitless scale-radius ratio (r50,Hα/r50,cont), which compares the extent of ongoing star formation to previous star formation. With this metric, we find that the fraction of galaxies with centrally concentrated star formation increases with environment density, from ∼ 5 ± 4 per cent in low-density environments (log10(Σ5/Mpc2) < 0.0) to 30 ± 15 per cent in the highest density environments (log10(Σ5/Mpc 2) > 1.0). These lines of evidence strongly suggest that with increasing local environment density, the star formation in galaxies is suppressed, and that this starts in their outskirts such that quenching occurs in an outside-in fashion in dense environments and is not instantaneous. Peer reviewed